Camões revisitado: sobre que farei com este livro? de José Saramago - Pereira, Marcio Roberto [UNESP] (My University, 2014)
The objective of this work is to analyze the literary construction of Camões in the work Que farei com este livro?, by José Saramago. By difficulty in publishing his magnum opus, Os Lusíadas, Camões traverses the various Portuguese authorities in order to be able to give concreteness to his work years in exile. Using historical aspects and gaps on the biography of Camões, Saramago creates a work that shows the inertia that reigned in Portugal after the great conquests. Work of counterpoint between past and present, Que farei com este livro? represents an important reflection on the role of the writer and their challenges in times of decadence.

O objetivo deste trabalho é analisar a construção literária de Camões na obra Que farei com este livro?, de José Saramago. Por causa da dificuldade em publicar sua obra máxima, Os Lusíadas, Camões percorre as diversas instâncias portuguesas no intuito de conseguir dar concretude ao seu trabalho de anos no exílio. Recorrendo a aspectos históricos e lacunas sobre a biografia de Camões, Saramago cria uma obra que mostra a inércia que reinava em Portugal após as grandes conquistas. Obra de contraponto entre o passado e o presente, Que farei com este livro? representa uma importante reflexão sobre o papel do escritor e seus desafios em momentos de decadência.
Camões revisited: about que farei com este livro? by José Saramago
Keywords: José Saramago; Representation; Portuguese Literature; José Saramago; Representação; Literatura Portuguesa